2010
DOI: 10.1111/j.1365-2265.2010.03827.x
|View full text |Cite
|
Sign up to set email alerts
|

ORIGINAL ARTICLE: Assessment of cardiac valve dysfunction in patients receiving cabergoline treatment for hyperprolactinaemia

Abstract: Our data demonstrates that there is no association between cabergoline treatment for hyperprolactinaemia and valvulopathy. This study therefore supports continued use of low-dose cabergoline for patients with hyperprolactinaemia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
28
5
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(37 citation statements)
references
References 32 publications
3
28
5
1
Order By: Relevance
“…Moreover, even though trivial valvulopathy was slightly increased after long-term treatment, the overall prevalence of mitral (25%) and tricuspid (45%) valvular regurgitations has been found to be not increased when compared with the general population, in line with the results of the Framingham Heart Study (45), showing an overall prevalence of any degree of mitral and tricuspid regurgitations in 88-91 and 82-86% of the general population respectively. In our series, the prevalence of mild aortic insufficiency (2.5%) was similar to the 2.7% reported by Tan et al (22), the 2% recorded by Elenkova et al (25), and the 3.9% found by Córdoba-Soriano et al (26) and within the 0-14% described in the general population (45). In our cohort of patients, none developed significant pulmonic regurgitation or arterial pulmonic hypertension, and none showed moderate or severe regurgitation of mitral and tricuspid valve.…”
Section: Discussionsupporting
confidence: 76%
See 3 more Smart Citations
“…Moreover, even though trivial valvulopathy was slightly increased after long-term treatment, the overall prevalence of mitral (25%) and tricuspid (45%) valvular regurgitations has been found to be not increased when compared with the general population, in line with the results of the Framingham Heart Study (45), showing an overall prevalence of any degree of mitral and tricuspid regurgitations in 88-91 and 82-86% of the general population respectively. In our series, the prevalence of mild aortic insufficiency (2.5%) was similar to the 2.7% reported by Tan et al (22), the 2% recorded by Elenkova et al (25), and the 3.9% found by Córdoba-Soriano et al (26) and within the 0-14% described in the general population (45). In our cohort of patients, none developed significant pulmonic regurgitation or arterial pulmonic hypertension, and none showed moderate or severe regurgitation of mitral and tricuspid valve.…”
Section: Discussionsupporting
confidence: 76%
“…Results from 15 observational studies investigating the risk of fibrotic valvulopathy in hyperprolactinemic patients treated with CAB have been published to date (13,14,15,16,17,18,19,20,21,22,23,24,25,26,27). Two of them (15,20) have shown no relevant findings.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Cabergoline, which possesses a complete 5HT 2b agonistic activity, is the drug of choice in the treatment of prolactinomas, but the results of observational studies investigating the risk of FVHD in these patients are still controversial. Some of them have reported no relevant findings (8,9,10,11,12), five trials have observed clinically insignificant valvular changes (13,14,15,16,17), and only one study has reported an increased prevalence of moderate tricuspid regurgitation with a cumulative dose-dependent risk (18). Published data on the potential profibrotic effect of bromocriptine, a partial 5HT 2b agonist, are exclusively limited (19).…”
Section: Introductionmentioning
confidence: 99%